Effect of gastroretentive gabapentin (Gralise) on postmastectomy pain syndrome: a proof-of-principle open-label study. (May 2017) - Belfer, Inna; Pollock, Netanya I.; Martin, Jodi L.; Lim, Katherine G.; De La Cruz, Carolyn; Van Londen, Gijsberta; Nunziato-Virga, Stephanie R.; Stranieri, Katherine; Brufsky, Adam M.; Wang, Haibin
Abstract: Introduction: Chronic pain is a common and debilitating complication following breast surgery. One of the most challenging for treatment is the neuropathic pain condition, postmastectomy pain syndrome (PMPS). Gabapentin is a pharmacotherapy for neuropathic pain disorders; however, its once-daily, gastroretentive formulation, Gralise, has not been evaluated in PMPS. Objective: To evaluate the safety and effectiveness of Gralise in patients with moderate-to-severe PMPS. Methods: The primary effectiveness endpoint was a change in the worst pain intensity score from baseline to completion of 8 weeks of Gralise therapy. The secondary endpoints included the change in mood, coping behavior, sleep, and function. Sensitivity to experimental stimuli was tested before and after treatment via quantitative sensory testing. The incidence and type of adverse event were used to evaluate the safety and tolerability of Gralise. Results: Twenty-one patients with confirmed moderate-to-severe PMPS were enrolled. Nineteen of 21 (90.5%) patients completed the 8-week treatment with Gralise. A significant positive change was found in pain intensity, pain impact, and sleep. There was no change in sensory testing scores. Of total, 63.16% of patients reported reduction in present pain, 78.95% in average pain, 89.47% in worst pain, and 84.21% in overall pain severity at posttreatment visit. No significant adverse effects were noted in the study. Limitations: Variation in type of breast surgery, small sample size, lack of placebo control. Conclusion: There was a significant improvement in pain and sleep, and Gralise was well tolerated in patients with PMPS. Further investigation is warranted. Abstract : Supplemental Digital Content is Available in the Text.An 8-week treatment with 1800 mg of Gralise decreased the severity of postmastectomy pain syndrome and the degree of sleep impairment and catastrophizing behavior.